2010
DOI: 10.1136/ip.2010.029215.755
|View full text |Cite
|
Sign up to set email alerts
|

European map of prevalence rates on elder abuse and its impact for future research

Abstract: IntroductionWHO and the International Network of the Prevention of Elder Abuse have recognised the abuse of older people as a significant global problem. Notwithstanding this recognition, generally the issue of elder abuse does not emerge as a major theme in research nor in the work of policymakers.MethodThis research is part of the “prevalence study of Abuse and Violence against Older Women” (AVOW) which is funded by the EU's Daphne III programme. The AVOW-study aims to provide knowledge about the prevalence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 0 publications
1
28
0
1
Order By: Relevance
“…A further consideration regarded the awareness of different levels of development of the prevalence of research on elder abuse and neglect throughout the European countries , with Italy having just begun to investigate this aspect at national level. Moreover, there was evidence that estimated prevalence and other characteristics of elder abuse may vary between countries and also between studies within the same country, thus probably reflecting real cross-national and cross-cultural variations in rates of elder abuse, as well as differences in definitions and categories of elder abuse, and in instruments used to measure the phenomenon (Cooper et al, 2008;De Donder et al, 2011;Daly, Merchant, & Jogerst, 2011).…”
Section: The Italian Contextmentioning
confidence: 95%
“…A further consideration regarded the awareness of different levels of development of the prevalence of research on elder abuse and neglect throughout the European countries , with Italy having just begun to investigate this aspect at national level. Moreover, there was evidence that estimated prevalence and other characteristics of elder abuse may vary between countries and also between studies within the same country, thus probably reflecting real cross-national and cross-cultural variations in rates of elder abuse, as well as differences in definitions and categories of elder abuse, and in instruments used to measure the phenomenon (Cooper et al, 2008;De Donder et al, 2011;Daly, Merchant, & Jogerst, 2011).…”
Section: The Italian Contextmentioning
confidence: 95%
“…Face validity was ensured based on four aspects: Indicators were derived from an extensive international literature review (De Donder et al, 2011). A cross-cultural academic expert panel reviewed these items, agreeing that they met the theoretical perspectives of elder abuse.…”
Section: Measurement Instrumentmentioning
confidence: 99%
“…Nevertheless, elder abuse is often defined as ''a single or repeated act, or lack of appropriate action, occurring within any relationship where there is an expectation of trust which causes harm or distress to an older person'' (Action on Elder Abuse, 1995, p. 5;World Health Organization [WHO], 2002). And elder abuse is most often conceptualised as a multifaceted phenomenon comprising several types of abuse: neglect, emotional, financial, physical, sexual abuse, and violation of personal rights (Cooper, Selwood, & Livingston, 2008;De Donder et al, 2011). Because elder abuse is a significant global problem, it needs to be assessed and monitored through accurate (and) brief procedures (Bennett, Levin, & Straka, 2002).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although some systematic reviews developed in the past decade identified this conceptual and methodological diversity (Cooper et al, 2008;De Donder et al, 2011), an internationally adopted concept definition is still lacking. The growth of prevalence studies, as indicated by Biggs and Haapala (2010), is not necessarily accompanied by the conceptual development of the problem, and the field has largely stood still.…”
Section: Introductionmentioning
confidence: 99%